The Influence Of Perceived Occupational Stress On The Organizational Citizenship Behaviour Of Bankers In Ikeja, Lagos State - Odunayo. T, Arogundade; Oladipupo., Lawal (European Scientific Journal, ESJ, 2016)
This study explored the influence of perceived occupational stress on organizational citizenship behaviour among bankers. A simple random sampling technique was used to select three hundred (300) participants (M=135; F=165) from twelve (12) banks in Ikeja, Lagos State, Nigeria. Data for the study were collected using Job Stress Scale (JSS) and Organizational Citizenship behaviour Checklist (OCBC). The data was analysed using Pearson correlation, and t-test. The results revealed that there is no significant difference between the organizational citizenship behaviour of bankers with higher stress levels and that of bankers with lower stress levels. This implies that bankers’ reactions to Organizational Citizenship Behaviour (OCB) are not a function of stress levels. The study however confirms an inverse relationship between stress and Organizational citizenship Behaviour. The findings of the study reveal that there is no significant difference between the Organizational Citizenship Behaviour (OCB) of male and female bankers. Finally, the findings reveal that older bankers between age 41 and 50 years expressed higher levels of organizational citizenship behaviour than younger bankers between 31 and 40 years. The implications of these findings substantiate the importance of having organizational psychologists in banks to assess and enhance variables that can promote helping behaviours which is the key to better work outcomes and accomplishment of organizational objectives.